2018
DOI: 10.1016/j.conbuildmat.2018.09.120
|View full text |Cite
|
Sign up to set email alerts
|

The use of copper slags as an aggregate replacement in asphalt mixes with RAP: Physical–chemical and mechanical behavioural analysis

Abstract: Copper slag (CS) is a derivative of copper production that is mainly composed of heavy metals. The large amount of this material accumulated around the world entails a serious environmental danger. Its use as a replacement of mineral aggregate in asphalt mixtures would allow to increase the durability and resistance, taking advantage of its physical-chemical properties. In this research, physicochemical analyses of different combinations of CS, reclaimed asphalt pavements (RAP), asphalt cement and aggregates b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The smaller sizes of CS analysed have low adhesion with the binder, and reduce the IDT strength in both dry and wet conditions. CS has an acidic character due to its composition (Raposeiras et al, 2018), similar to the aggregate character in the reference samples, and the CS also has slightly rough faces, which accentuate the loss of adhesiveness, especially when dealing with the smallest particles in the mixture.…”
Section: Moisture Damage Testmentioning
confidence: 92%
See 1 more Smart Citation
“…The smaller sizes of CS analysed have low adhesion with the binder, and reduce the IDT strength in both dry and wet conditions. CS has an acidic character due to its composition (Raposeiras et al, 2018), similar to the aggregate character in the reference samples, and the CS also has slightly rough faces, which accentuate the loss of adhesiveness, especially when dealing with the smallest particles in the mixture.…”
Section: Moisture Damage Testmentioning
confidence: 92%
“…Previous research of asphalt mixtures which incorporate RAP and CS showed a beneficial effect of the inclusion of both materials in dense graded asphalt mixtures in terms of thermal susceptibility and ageing (Raposeiras et al, 2016(Raposeiras et al, , 2018. Although CS does not modify the behaviour of the binder and its rheological characteristics at different temperatures, it can help to keep the mix more stable against these changes in pavement temperature due to its thermal behaviour, reducing the variability of durability as a function of temperature variation.…”
Section: Introductionmentioning
confidence: 99%
“…AMs mostly consist of coarse aggregates and bitumen, but also a certain percentage of filler must be added and balanced. A proper amount of filler helps both in reducing the mixture porosity and in hardening the bitumen, improving the overall performance in terms of rutting and shoving response [ 2 , 3 , 4 , 5 , 6 , 7 ]. Conversely, an excessive amount of filler decreases the aggregate content, thus leading to a strength reduction [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Purohit et al [16] explored the use of RAP and recycled concrete aggregates (RCA) in asphalt mixture, evaluating the performance of asphalt mixture containing RAP and RCA by using Marshall and moisture susceptibility test, and indicating an advantage over the conventional mixes. Ramos et al [17] reported the asphalt mixture containing copper slag (CS) and RAP, and indicated that asphalt mixes stability improved with ranges from 45% to 55% of recycled material. Therefore, to reduce the consumption of natural aggregates, it is necessary to further explore the possibility of replacing natural aggregates with other wastes materials to produce RHMA, and expand the waste types.…”
Section: Introductionmentioning
confidence: 99%